VET and recruitment - car service and healthcare : Korea and Germany - Lee, Dong-Im [Verfasser]; Kim, Mee-Souk [Verfasser]; Kim, Ahn Kook [Verfasser]; Grollmann, Philipp [Verfasser]; Geiben, Marthe [Verfasser] (My University, 2014)
This report refers to the research project "Patterns of Recruitment and Inducation" (INDUCT) that BIBB started in 2009. With the second phase of the project (INDUCT II) which commenced in July 2012, the Republic of Korea joined the project. KRIVET and BIBB signed a Memorandum of Understanding (MOU) for a "Corporate Survey on the Recruitment and VET of helathcare and car serrvice Industry" with the aim to analyze their respective nations' recruitment customs and practices. "Two industries - car service and healthcare - were selected for the study. The two sectors were surveyed in both nations with identical questionnaires. The inducation of career entrants (inducation duration and process) was analyzed on the survey results; based on certain hypotheses, emphasis was placed on factors influencing the induction duration." (Autors' abstract, BIBB-Doku)
Keywords: G 1.3.2.2.3 Zweite Schwelle, in Arbeit; S 5.3 Personalentwicklung; S 6.2.3 Metallerzeugung und -bearbeitung, Maschinenbau, Montierberufe (inkl. fahrzeugtechnischer Berufe); S 6.4.5 Gesundheits-, Sozial- und Erziehungsberufe; T 3.4 Befragung; I 2.1 Deutschland; I 2.3.4 Asien; Berufseinmündung; Zweite Schwelle; Betrieb; Personalgewinnung; Mittlere Qualifikation; Berufsanfänger; Fahrzeugtechnischer Beruf; Pflegeberuf; Befragung; Internationaler Vergleich; Bundesrepublik Deutschland; Südkorea